Composite sealing material, preparation method of composite sealing material, double-glass assembly and manufacturing method of double-glass assembly

By providing a composite sealing material, including gaskets and high viscosity sealing slurry film, the technical difficulties of glass wide-slit laser sealing of double-glass components are solved, and efficient water vapor insulation performance improvement and long-term stability are achieved.

CN119677177APending Publication Date: 2025-03-21SHANGHAI NEXOLAR NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411758741.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

There are technical problems in glass wide-slit laser sealing of double-glass components. The bonding strength of traditional sealing materials is insufficient and aging, resulting in a degradation of water vapor insulation performance and the high-temperature glue discharge process is complicated.

Method used

A composite sealing material is provided, including a gasket strip and a sealing slurry film disposed on both sides of the gasket strip. The dry film thickness of the sealing slurry film is more than 5 μm, and is suitable for laser sealing of double-glass components. The material is prepared by single-sided construction method or double-sided simultaneous construction method, and low-melting glass and organic carrier are used during laser sealing to improve viscosity.

Benefits of technology

The dense sealing of wide glass joints of double-glass components is achieved, which improves the water vapor insulation performance and increases the water vapor transmission rate by at least one order of magnitude, meets the requirements of high water vapor insulation, and maintains high efficiency performance for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677177A_ABST
    Figure CN119677177A_ABST
Patent Text Reader

Abstract

The invention provides a composite sealing material and a preparation method thereof, and a double-glass assembly and a manufacturing method thereof, the composite sealing material comprises a filler strip and sealing slurry films respectively arranged on two opposite side surfaces of the filler strip, and the dry film thickness of the sealing slurry films is more than 5 [mu] m. The invention further provides a double-glass assembly, the composite sealing material is arranged between the front plate glass and the back plate glass of the double-glass assembly, and the sealing slurry film in the composite sealing material is sealed with the front plate glass and the back plate glass in a laser sealing mode. The composite sealing material is used for laser sealing of a glass wide gap of a double-glass assembly, so that the glass wide gap of the double-glass assembly can be tightly sealed, the double-glass assembly has excellent water vapor insulation performance, the requirement of high water vapor insulation of the double-glass assembly is met, the excellent water vapor insulation performance can be kept for a long time, and the service life of the double-glass assembly is prolonged. And therefore, high-efficiency, high-reliability and lasting operation of the assembly can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite sealing material and a preparation method thereof, and a double-glass component and a manufacturing method thereof, belonging to the technical field of solar cell components. Background Art

[0002] The double-glass module is named because both the front and back panels are made of glass, and its water-blocking performance is significantly improved compared to the single-glass module. The weak point of water vapor intrusion in the double-glass module becomes the gap between the two glasses. The width of this gap varies slightly with the different battery packs in the middle, but the spacing between the front and back glass of the double-glass module is often greater than or equal to 0.5mm, which makes it extremely difficult to use traditional laser sealing methods. The glass of the double-glass module is already in a tempered state during lamination. If the slurry is applied to the glass alone, it will experience a high temperature of 300-450℃ during the debonding process, which will reduce the strength of the tempered glass; if the gap is filled by squeezing glue, in addition to heating the entire component to make debonding difficult, it will also cause the battery pack to experience high temperature shock. Both of these situations limit the application of sealing slurry to the component. The above main problems are concentrated in two aspects: First, the gap is too wide, and the filled glass paste cannot achieve true debonding, which causes a large amount of smoke and dust to be generated during the subsequent laser sealing process, and causes pores throughout the film layer; second, the melting depth of laser sealing is limited, and it is impossible to melt the excessively thick glass layer.

[0003] At present, the common glass laser sealing gap width will not exceed 150μm. The main reasons are also from two aspects. First, the hot melting depth of the laser-melted sealing body is limited, and it is impossible to melt very thick sealing materials; second, the sealing material is too thick, generally in the form of slurry, and is attached to the substrate after construction and drying. The dry film formed in this way is prone to melt isolation during the laser melting process, which in turn creates pores in the entire film layer.

[0004] At present, for the water-blocking sealing of double-glass components, in addition to using high water-blocking adhesive film for battery pack sealing, butyl glue 4 is usually squeezed into the gap between the glasses before lamination, and the battery pack 3 between the front glass 1 and the back glass 2 is sealed with butyl glue 4, and then the outside is encapsulated with silicone 5 combined with an aluminum frame 6. The specific structural schematic diagram is shown in the following figure: Figure 4 As shown. Although this sealing method can meet the short-term water vapor insulation sealing problem of double-glass modules, butyl glue itself is not sticky, and the bonding strength to the front glass and back glass of double-glass modules is weak. As the use time of double-glass modules increases, organic materials such as butyl glue will age, which will make the sealing of double-glass modules worse, and the water vapor barrier effect, that is, the water vapor insulation performance will be greatly weakened. Moreover, the cost of high-resistance water-resistant film itself is much higher than that of ordinary film. When combined with high-resistance water-resistant butyl glue, although the two can meet the timeliness requirements of modules, combined with cost considerations, it is by no means the best choice.

[0005] Therefore, it is particularly important to further improve the water vapor insulation performance of photovoltaic modules while meeting the requirements of high reliability and long service life. To this end, providing a new composite sealing material for double-glass module glass wide seam laser sealing and its preparation method, and a double-glass module and its manufacturing method has become a technical problem that needs to be solved in this field. Summary of the invention

[0006] In order to solve the above-mentioned shortcomings and deficiencies, the object of the present invention is to provide a composite sealing material and a preparation method thereof and a double-glass component and a manufacturing method thereof.

[0007] In order to achieve the above objectives, on the one hand, the present invention provides a composite sealing material, wherein the composite sealing material includes a gasket and a sealing slurry film respectively arranged on two opposite sides of the gasket, and the dry film thickness of the sealing slurry film is greater than 5μm.

[0008] In the composite sealing material described above in the present invention, the pad is a dense strip material, and its thickness can be adjusted within the range of 0.5-3.2 mm depending on the thickness of the battery pack in the double-glass assembly (the thickness refers to the extension in the longitudinal direction perpendicular to the plane where the battery pack is located); the width is between 2-10 mm, preferably between 2-5 mm.

[0009] As a specific embodiment of the composite sealing material described above in the present invention, the material of the gasket strip includes glass or ceramics, etc. Preferably, the glass includes float glass or embossed glass, etc.

[0010] As a specific embodiment of the composite sealing material described above, the expansion coefficient of the gasket strip is close to or even the same as that of the front glass and the back glass. In some embodiments, the gasket strip is made of the same material as that of the front glass and the back glass.

[0011] In the composite sealing material of the present invention, the thickness of the sealing slurry film respectively arranged on the two opposite sides of the gasket strip can be the same or different. For example, when the gasket strip is made of float glass, it is preferred that the thickness of the sealing slurry film on the two opposite sides of the gasket strip is the same, that is, the two layers of sealing slurry film are symmetrically distributed; when the gasket strip is made of embossed glass, it is preferred that the sealing slurry film on the embossed side of the embossed glass is thicker, at least covering the embossed pattern on the embossed side. Of course, in either case, the dry film thickness of the sealing slurry film must be above 5 μm.

[0012] As a specific embodiment of the composite sealing material described above in the present invention, the dry film thickness of the sealing slurry film is 5-150 μm.

[0013] As a specific embodiment of the composite sealing material described above, the sealing slurry film contains low-melting-point glass. In some specific embodiments of the present invention, the melting temperature of the low-melting-point glass is 330-430°C, which is also the temperature of laser sealing used in the subsequent production of double-glass components.

[0014] The sealing slurry film in the composite sealing material provided by the present invention can be sealed by laser, so the composite sealing material is suitable for laser sealing of wide seams of double-glass components. For example, in some embodiments of the present invention, in a double-glass component, the distance between the front glass and the back glass is greater than or equal to 0.5 mm.

[0015] On the other hand, the present invention also provides a method for preparing the composite sealing material described above, wherein the preparation method includes a single-side construction method and a double-side simultaneous construction method:

[0016] The one-side construction method includes: applying the sealing slurry on the first side of the cushion strip and then drying it to ensure that the sealing slurry is completely shaped, applying the sealing slurry on the second side of the cushion strip opposite to the first side after cooling and then drying it to ensure that the sealing slurry is completely shaped, and then cooling to obtain the composite sealing material;

[0017] The double-sided simultaneous construction method includes: applying sealing slurry on two opposite sides of the cushion strip at the same time and then drying the slurry to ensure that the sealing slurry is completely shaped, and then performing a debonding process on the shaped product to obtain the composite sealing material.

[0018] As a specific embodiment of the preparation method described above of the present invention, in the single-side construction method, the coating includes screen printing (silk screen printing) or roller coating, etc.

[0019] As a specific embodiment of the preparation method described above in the present invention, in the double-sided simultaneous construction method, the coating includes dipping or spraying.

[0020] As a specific embodiment of the preparation method described above, the drying temperature is 180-280° C. The present invention does not make specific requirements on the drying time, and can be reasonably adjusted as needed, as long as the purpose of drying can be achieved. For example, in some specific embodiments of the present invention, the drying time can be 30 minutes.

[0021] As a specific embodiment of the preparation method described above, the debinding treatment includes: firstly performing debinding treatment at 280-350°C, and then performing debinding treatment at 350-450°C. The present invention does not make specific requirements on the time of the two-step debinding treatment, and can be reasonably adjusted as needed, as long as the purpose of debinding can be achieved. For example, in some specific embodiments of the present invention, the time of the first step debinding can be 1 hour, and the time of the second step debinding can be 2 hours.

[0022] The preparation method described above in the present invention does not make specific requirements on the coating thickness of the sealing slurry, that is, the thickness of the wet film, and can be reasonably adjusted as needed, as long as the dry film thickness of the obtained sealing slurry film is ensured to be above 5μm, preferably 5-150μm, and more preferably 20-50μm, so as to ensure that a better sealing effect can be achieved in the subsequent laser sealing process.

[0023] As a specific embodiment of the above-mentioned preparation method of the present invention, the sealing slurry comprises low-melting-point glass and an organic carrier, and the solid content thereof is above 60 wt %.

[0024] As a specific embodiment of the preparation method described above of the present invention, wherein the organic carrier includes an organic solvent and a dissolving resin, the organic solvent is mainly used for pulping, and the dissolving resin is mainly used to increase the viscosity of the slurry. The present invention does not make specific requirements on the specific substances of the organic solvent and the dissolving resin and the respective amounts of the two, and can be reasonably selected and adjusted as needed. For example, in some embodiments of the present invention, the organic solvent may include diethylene glycol butyl ether, tripropylene glycol methyl ether, diethylene glycol butyl ether acetate, pine alcohol and dipropylene glycol methyl ether, etc., and the dissolving resin may include cellulose, acrylic resin, etc.

[0025] In some specific embodiments of the present invention, the low-melting-point glass is a low-melting-point glass powder, which is a V2O5-Bi2O3 system, has an expansion coefficient of 70-80, and a Tg temperature of 280-400°C.

[0026] When preparing the sealing slurry, low melting point glass powder is mixed in an organic carrier and ground into a uniform slurry with a viscosity of 25000-95000 mPa·S and a scraper fineness of <15 μm.

[0027] As a specific embodiment of the preparation method described above, the expansion coefficient of the sealing slurry system is close to or even the same as that of the gasket, the front glass plate and the back glass plate.

[0028] The present invention rationally designs the structure of the composite sealing material and combines it with the design of the glass paste that can be laser-sealed, that is, the design of the sealing paste formula, so that the composite sealing material provided by the present invention is suitable for laser sealing of wide glass seams of double-glass components, and the obtained double-glass components have better process compatibility and water vapor insulation performance.

[0029] On the other hand, the present invention also provides a double-glass component, comprising a front glass panel, a back glass panel and a battery pack arranged between the front glass panel and the back glass panel, wherein the double-glass component also includes the composite sealing material mentioned above, the composite sealing material is arranged between the front glass panel and the back glass panel, and the sealing slurry film layer in the composite sealing material is sealed to the front glass panel and the back glass panel by laser sealing.

[0030] The double-glass component of the present invention can be sealed only by using the composite sealing material, or can be sealed by partially using the composite sealing material in combination with existing conventional sealing materials.

[0031] When only the composite sealing material is used for sealing, the double-glass assembly includes a front glass panel, a back glass panel and a battery pack arranged between the front glass panel and the back glass panel, wherein the front glass panel and the back glass panel respectively include a first surface and a second surface arranged in a facing manner, and the first surface and the second surface are respectively provided with a first packaging area and a second packaging area corresponding thereto along their entire circumference, wherein the composite sealing material is arranged between the first packaging area and the second packaging area, and the sealing slurry film in the composite sealing material is sealed with the front glass panel and the back glass panel by laser sealing to encapsulate the battery pack.

[0032] When the composite sealing material is partially used and combined with existing conventional sealing materials for sealing, the composite sealing material and the existing conventional sealing material are arranged between the first packaging area and the second packaging area as needed, and the sealing slurry film in the composite sealing material is sealed with the front glass and the back glass by laser sealing to encapsulate the battery pack.

[0033] As a specific embodiment of the double-glass component described above in the present invention, in the double-glass component, the double-glass component also includes a heat-resistant and water-insulating material layer, which is arranged between the composite sealing material and the battery pack. At this time, the present invention uses the heat-resistant and water-insulating material layer in combination with the composite sealing material, performs laser sealing of the front glass and the back glass through the composite sealing material, and fills the heat-resistant and water-insulating material layer on the inner side of the composite sealing material near the battery pack to prevent heat transfer during laser sealing and to fix trace amounts of water vapor in the component; that is, the heat-resistant and water-insulating material layer used in the present invention can, on the one hand, isolate the heat during laser sealing from transferring toward the battery pack, and on the other hand, can fix trace amounts of water vapor that has not been completely discharged in the battery pack. Through this solution, the problem of wide-slit laser sealing of double-glass components can be better solved, and the water vapor barrier performance of the component can be further improved.

[0034] In the double-glass assembly described above in the present invention, when the double-glass assembly includes a heat-resistant and water-insulating material layer, the heat-resistant and water-insulating material layer is located between the composite sealing material and the battery pack, and may or may not be in contact with the battery pack; it may or may not be in contact with the composite sealing material.

[0035] In the above double-glass component of the present invention, the specific surface area, porosity and average particle size of the heat-insulating and water-insulating material can be appropriately adjusted according to the component requirements. Preferably, as a specific embodiment of the above double-glass component of the present invention, in the double-glass component, the specific surface area of ​​the heat-insulating and water-insulating material is greater than 0.1 m 2 / g, and the porosity is greater than 30%. As a specific embodiment of the double-glass component of the present invention, in the double-glass component, the average particle size of the heat-insulating and water-insulating material is less than 10 μm.

[0036] As a specific embodiment of the double-glass component described above in the present invention, in the double-glass component, the heat-resistant and water-insulating material includes zeolite and / or inorganic molecular sieve and the like.

[0037] As a specific embodiment of the double-glass assembly described above in the present invention, the thickness of the heat-resistant and water-insulating material layer is 0.5-3.2 mm;

[0038] And / or the width of the heat-resistant and water-insulating material layer is 2-10 mm.

[0039] As a specific embodiment of the double-glass assembly described above, in the double-glass assembly, the distance between the front glass and the back glass is greater than or equal to 0.5 mm.

[0040] In some preferred embodiments of the present invention, the material of the front glass and the back glass used in the double-glass assembly is similar to, and more preferably the same as, the material of the gasket in the composite sealing material.

[0041] In another aspect, the present invention further provides a method for manufacturing the double-glass component described above, wherein the manufacturing method comprises:

[0042] The composite sealing material is first placed between the front glass and the back glass, and then laminated. After the lamination is completed, the sealing slurry film in the composite sealing material is laser sealed with the front glass and the back glass to seal the front glass, the back glass and the composite sealing material into a whole to obtain the double glass assembly.

[0043] As a specific embodiment of the manufacturing method of the double-glass component described above in the present invention, the manufacturing method further comprises:

[0044] First, a heat-resistant and water-insulating material layer is placed between the front glass and the back glass and close to the side wall of the battery pack. Then, the composite sealing material is placed between the front glass and the back glass and close to the heat-resistant and water-insulating material layer, and then laminated. After lamination, the sealing slurry film in the composite sealing material is laser-sealed with the front glass and the back glass to seal the front glass, the back glass and the composite sealing material into a whole to obtain the double-glass component.

[0045] Among them, the present invention does not make specific requirements on the operation of laser sealing and the process parameters used in the laser sealing process. In the actual production process, the laser sealing parameters can be determined according to the melting temperature of the specific glass paste and taking into account comprehensive factors such as the processing time and temperature that causes the least damage to the solar panel as possible.

[0046] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0047] The present invention provides a composite sealing material and uses it for laser sealing of wide glass seams of double-glass components, which solves the problem of high temperature (300-500°C) adhesive discharge in the prior art and the technical difficulties in the wide-seam glass sealing of the existing double-glass components. Not only can the wide glass seams of the double-glass components be densely sealed, but also the components have excellent water vapor insulation performance. The water vapor insulation performance (water vapor permeability) can be improved by at least one order of magnitude compared with the double-glass components obtained by sealing with the traditional butyl adhesive solution, meeting the high water vapor insulation requirements of the double-glass components. In addition, the excellent water vapor insulation performance can be maintained for a long time, thereby providing a guarantee for the high reliability and long-lasting operation of the components under high efficiency and high power conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 This is a schematic diagram of the structure of the composite sealing material provided in Example 1 of the present invention.

[0050] Figure 2 This is a schematic diagram of the structure of a double-glass assembly provided in Example 2 of the present invention.

[0051] Figure 3 This is a schematic diagram of the structure of a double-glass assembly provided in Example 3 of the present invention.

[0052] Figure 4 This is a schematic structural diagram of a double-glass assembly according to the prior art, i.e., Comparative Example 1.

[0053] Figure 5 This is a schematic structural diagram of the double-glass assembly provided for Comparative Example 2.

[0054] Description of main figures:

[0055] 1. Front glass;

[0056] 2. Back panel glass;

[0057] 3. Battery pack;

[0058] 4. Butyl rubber;

[0059] 5. Silicone;

[0060] 6. Aluminum frame;

[0061] 7. Composite sealing materials;

[0062] 71. Pads;

[0063] 72. a first sealing slurry film;

[0064] 73. A second sealing slurry film;

[0065] 8. Heat-proof and water-insulating material layer. DETAILED DESCRIPTION

[0066] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0067] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "inner", "outer", "middle", "left", "right", "top" and "bottom" are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0068] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0069] In addition, the terms "disposed" and "connected" should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0070] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0071] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0072] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0073] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0074] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0075] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and Examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0076] Example 1

[0077] This embodiment provides a composite sealing material, and its structure schematic diagram is as follows Figure 1 As shown, from Figure 1 It can be seen that the composite sealing material 7 includes a gasket 71, a first sealing slurry film 72 and a second sealing slurry film 73, and the first sealing slurry film 72 and the second sealing slurry film 73 are respectively arranged on the upper surface and the lower surface of the gasket 71;

[0078] The dry film thickness of the first sealing slurry film 72 and the second sealing slurry film 73 are both 50 μm, and both contain low-melting-point glass;

[0079] The gasket strip 71 has a thickness of 0.8 mm and a width of 4 mm, and is made of ultra-clear float glass.

[0080] The composite sealing material provided in this embodiment can be prepared by a single-side construction method or a double-side simultaneous construction method:

[0081] The one-side construction method includes: using screen printing or roller coating, firstly, applying a sealing slurry with a thickness of 75 μm on the upper surface or lower surface of the cushion strip 71 to form a first wet film, and then placing the cushion strip 71 in an oven and baking it at 200° C. for 30 minutes to ensure that the sealing slurry is completely formed and has a certain strength; after taking out the cushion strip 71, placing it in a room temperature environment, and after it cools to below 30° C., applying a sealing slurry with a thickness of 75 μm on the lower surface or upper surface of the cushion strip 71 to form a second wet film, and then placing the coated cushion strip 71 in an oven again, drying it at 200° C. for 30 minutes to ensure that the sealing slurry is completely formed and has a certain strength, and then cooling it to obtain the composite sealing material;

[0082] The double-sided simultaneous construction method includes: using a dipping or spraying method, simultaneously applying a sealing slurry with a thickness of 75 μm on the upper surface and the lower surface of the cushion strip 71 to form a first wet film and a second wet film respectively, and then placing the cushion strip 71 in an oven and baking it at 200° C. for 30 minutes to ensure that the sealing slurry is completely formed and has a certain strength;

[0083] Then the debinding treatment is carried out according to the following temperature and time:

[0084] 300°C, 1 hour;

[0085] 350° C., 2 hours, after the debinding treatment is completed, the composite sealing material is obtained;

[0086] The sealing slurry used in this embodiment includes low-melting point glass and an organic carrier, and its solid content is 78wt%; wherein the organic carrier includes an organic solvent and a dissolving resin, the organic solvent is mainly used for slurrying, and the dissolving resin is mainly used to increase the viscosity of the slurry. When preparing the sealing slurry, the low-melting point glass is mixed in the organic carrier and formed into a uniform slurry by grinding, so that its viscosity is 25000-95000mPa·S, and the scraper fineness is <15μm.

[0087] In this embodiment, the organic solvent is diethylene glycol butyl ether, the dissolving resin is an acrylic resin, and the low-melting point glass is a low-melting point glass powder, which is a V2O5-Bi2O3 system, with an expansion coefficient of 70-80, a Tg temperature of 280-400°C, and a melting temperature of 330-430°C.

[0088] Example 2

[0089] This embodiment provides a double-glass component, wherein the structural schematic diagram of the double-glass component is as follows: Figure 2 As shown, from Figure 2 It can be seen that it includes a front glass plate 1, a back glass plate 2, an aluminum frame 6, a battery pack 3 arranged between the front glass plate 1 and the back glass plate 2, and a composite sealing material 7; the front glass plate 1 and the back glass plate 2 are both made of ultra-white float glass, and the two respectively include a first surface and a second surface arranged in a facing manner, and the first surface and the second surface are respectively provided with a first packaging area and a second packaging area corresponding thereto along their entire circumference; the composite sealing material 7 is arranged between the first packaging area and the second packaging area, and the first sealing slurry film 71 and the second sealing slurry film 72 in the composite sealing material 7 are respectively sealed with the front glass plate 1 and the back glass plate 2 by laser sealing to encapsulate the battery pack 3; the aluminum frame 6 covers the entire outer edge of the front glass plate 1 and the back glass plate 2, that is, all around.

[0090] The double-glass component of this embodiment is manufactured by a manufacturing method including the following specific steps:

[0091] First, the composite sealing material provided in Example 1 is placed between the front glass and the back glass in the double-glass assembly, and then laminated. After lamination, the sealing slurry film in the composite sealing material is laser sealed with the front glass and the back glass to seal the front glass, the back glass and the composite sealing material into a whole, thereby realizing the encapsulation of the battery pack 3. Finally, the aluminum frame 6 is covered on the entire outer edge of the front glass 1 and the back glass 2, that is, all around, to obtain the double-glass assembly.

[0092] Example 3

[0093] This embodiment provides a double-glass component, wherein the structural schematic diagram of the double-glass component is as follows: Figure 3 As shown, the difference between it and embodiment 2 is only that:

[0094] The double-glass assembly of this embodiment further includes a heat-resistant and water-insulating material layer 8, which is disposed between the composite sealing material 7 and the battery pack 3;

[0095] The thickness of the heat-insulating and water-proofing material layer 8 is 0.8 mm and the width is 4 mm. The heat-insulating and water-proofing material is an inorganic molecular sieve with a specific surface area greater than 0.1 m2 / g, porosity greater than 30%, and average particle size less than 10μm.

[0096] Comparative Example 1

[0097] This comparative example provides a double-glass component, and its structural schematic diagram is as follows Figure 4 As shown, from Figure 4 It can be seen that the double-glass component uses butyl rubber 4 (which is usually squeezed into the gap between the front glass and the back glass before lamination) to seal the battery pack 3 between the front glass 1 and the back glass 2, and the outer edge is then encapsulated with silicone rubber 5 combined with an aluminum frame 6, wherein the materials of the front glass 1 and the back glass 2 are also ultra-clear float glass.

[0098] Comparative Example 2

[0099] This comparative example provides a double-glass component, wherein the structural schematic diagram of the double-glass component is as follows Figure 5 As shown, the difference between it and Comparative Example 1 is only that:

[0100] The double-glass assembly of this comparative example further includes a heat-resistant and water-insulating material layer 8, which is disposed between the butyl rubber 4 and the battery pack 3;

[0101] The thickness of the heat-insulating and water-proofing material layer 8 is 0.8 mm and the width is 4 mm. The heat-insulating and water-proofing material is an inorganic molecular sieve with a specific surface area greater than 0.1 m 2 / g, porosity greater than 30%, and average particle size less than 10μm.

[0102] Comparative Example 3

[0103] This comparative example provides a double-glass component, wherein the double-glass component is encapsulated by only a single-layer sealing slurry film, the dry film thickness of the single-layer sealing slurry film is 0.9 mm, and the rest is the same as Example 2.

[0104] Test Example 1

[0105] This test example uses conventional methods in the art to test the water vapor insulation performance (water vapor transmission rate) of the double-glass components provided by Examples 2 to 3 of the present invention and Comparative Examples 1 to 2.

[0106] For Example 2, the specific test process is as follows:

[0107] One long side of two pieces of glass (both with dimensions of 7cm x 5cm x 3.2mm) was sealed with the composite sealing material used in Example 2 of the present invention, and the short sides on both sides were sealed with AB glue. The inside of the two pieces of glass was a U-shape similar to a cup, and then they were placed on a moisture permeability tester for testing; the interfaces between the test piece and the test equipment were all sealed with AB glue to isolate water vapor;

[0108] The test conditions are: temperature 38±0.6°C, relative humidity 90±2% and time 24h.

[0109] For Example 3, the specific testing process is basically the same as that of Example 2, except that the heat-resistant and water-insulating material layer used in Example 3 is assembled on the bottom of the U-shaped piece formed by two pieces of glass.

[0110] For Comparative Example 1, the specific testing process is basically the same as that of Example 2, except that one long side of the two pieces of glass is sealed with the butyl adhesive used in Comparative Example 1.

[0111] For Comparative Example 2, the specific testing process is basically the same as that of Example 2, except that one long side of the two pieces of glass is sealed with the butyl rubber used in Comparative Example 2, and the heat-resistant and water-insulating material layer used in Comparative Example 2 is assembled on the bottom of the U-shaped piece formed by the two pieces of glass.

[0112] For Comparative Example 3, the specific testing process is similar to that of Example 2.

[0113] The test shows that the water vapor transmission rates of the double-glass assemblies provided by Examples 2 to 3 of the present invention and Comparative Examples 1 to 3 are 0.2-0.3 g / m 2 / Day or less, 0.15-0.25g / m 2 / Day or less, 2-3g / m 2 / Day, 0.8-1.2g / m 2 Less than / Day and more than 50g / m 2 / Day.

[0114] It can be seen that compared with the double-glass component obtained by sealing with the traditional butyl rubber solution in Example 1, the water vapor permeability of the heat-resistant and water-insulating material layer provided in Example 2 is reduced, indicating that the addition of the heat-resistant and water-insulating material layer can fix the trace amount of water vapor in the battery pack, and can block the external water vapor from invading the interior of the component to a certain extent, basically ensuring the efficient and reliable operation of the component. However, the water vapor permeability of the heat-resistant and water-insulating material layer provided in Example 2 is still significantly higher than that of the double-glass components using composite sealing materials and composite sealing materials and heat-resistant and water-insulating material layers in Examples 2-3 of the present invention, respectively. Compared with the double-glass components obtained by sealing with the traditional butyl rubber solution in Example 1, the water vapor insulation performance (water vapor permeability) of the double-glass components provided in Examples 2-3 of the present invention can be improved by at least one order of magnitude, indicating that it has excellent water vapor insulation performance, meets the high water vapor insulation requirements of the double-glass components, and can provide a guarantee for the high efficiency and high reliability and long-term operation of the components under high power conditions. The sealing of Comparative Example 3 is almost ineffective because, in the case of using only a single-layer sealing slurry film, the slurry shrinks and solidifies during the sealing process, forming a porous structure and obvious cracks. Such structural characteristics significantly increase its water vapor transmission rate. In addition, the glue removal process of Comparative Example 3 is difficult to operate during the sealing process, which greatly increases the difficulty of sealing.

[0115] Test Example 2

[0116] This test example examines the water vapor insulation stability of the double-glass components provided by Examples 2 to 3 of the present invention and Comparative Examples 1 to 2, respectively, and includes the following specific steps:

[0117] In this test example, high pressure, high heat and high humidity conditions (specific conditions are temperature 121°C, saturated vapor pressure, 100% humidity, 48h) are used to accelerate aging of the double-glass components provided by Examples 2-3 of the present invention and Comparative Examples 1-2, and then the water vapor insulation performance (water vapor transmission rate) is tested using the same test method as in Test Example 1. The test shows that the water vapor transmission rates of the double-glass components provided by Examples 2-3 of the present invention and Comparative Examples 1-2 after aging are 0.21-0.30 g / m 2 / Day or less, 0.15-0.25g / m 2 / Day or less, 5-6g / m 2 / Day and 1.8-2.6g / m 2 / Day or less).

[0118] It can be seen that compared with the double-glass component obtained by sealing with the traditional butyl rubber solution in Comparative Example 1, the water vapor permeability of the double-glass component provided by Example 1 of the present invention is better maintained and is almost unaffected by accelerated aging, indicating that it has excellent water vapor insulation performance and meets the high water vapor insulation requirements of the double-glass component.

[0119] In summary, the double-glass component provided in the embodiment of the present invention not only has excellent water vapor insulation performance, but also can maintain the excellent water vapor insulation performance for a long time, thereby providing a guarantee for the efficient, highly reliable and long-lasting operation of the component; while the double-glass component provided in Comparative Example 1 has aging of organic materials such as butyl rubber as its use time increases, which makes the sealing of the double-glass component worse, and the water vapor barrier effect, that is, the water vapor insulation performance, is also greatly weakened.

[0120] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A composite sealing material, characterized in that: The composite sealing material comprises a gasket strip and sealing slurry films respectively arranged on two opposite sides of the gasket strip, and the dry film thickness of the sealing slurry film is greater than 5 μm.

2. The composite sealing material according to claim 1, characterized in that: The thickness of the pad is 0.5-3.2 mm; And / or the width of the gasket is 2-10 mm.

3. The composite sealing material according to claim 1 or 2, characterized in that: The material of the gasket includes glass or ceramics. Preferably, the glass includes float glass or patterned glass.

4. The composite sealing material according to claim 1, characterized in that: The dry film thickness of the sealing slurry film is 5-150 μm.

5. The composite sealing material according to claim 1 or 4, characterized in that: The sealing paste film contains low-melting-point glass.

6. The method for preparing the composite sealing material according to any one of claims 1 to 5, characterized in that: The preparation method includes a single-side construction method and a double-side simultaneous construction method: The one-side construction method includes: applying the sealing slurry on the first side of the cushion strip and then drying it to ensure that the sealing slurry is completely shaped, applying the sealing slurry on the second side of the cushion strip opposite to the first side after cooling and then drying it to ensure that the sealing slurry is completely shaped, and then cooling to obtain the composite sealing material; The double-sided simultaneous construction method includes: applying sealing slurry on two opposite sides of the cushion strip at the same time and then drying the slurry to ensure that the sealing slurry is completely shaped, and then performing a debonding process on the shaped product to obtain the composite sealing material.

7. The preparation method according to claim 6, characterized in that: In the one-side separate construction method, the coating includes printing or roller coating.

8. The preparation method according to claim 6, characterized in that: In the double-sided simultaneous construction method, the coating includes dipping or spraying.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The drying temperature is 180-280°C.

10. The preparation method according to claim 6 or 8, characterized in that: The debinding treatment comprises: firstly performing the debinding treatment at 280-350° C., and then performing the debinding treatment at 350-450° C.

11. The preparation method according to any one of claims 6 to 8, characterized in that: The sealing paste comprises low melting point glass and an organic carrier, and the solid content of the sealing paste is above 60wt%.

12. A double-glass assembly, comprising a front glass, a back glass, and a battery pack disposed between the front glass and the back glass, characterized in that: The double-glass component also includes the composite sealing material described in any one of claims 1-5, and the composite sealing material is arranged between the front glass and the back glass, and the sealing slurry film layer in the composite sealing material is sealed with the front glass and the back glass by laser sealing.

13. The double-glass assembly according to claim 12, characterized in that: The double-glass component also includes a heat-resistant and water-insulating material layer, which is arranged between the composite sealing material and the battery pack.

14. The double-glass assembly according to claim 13, characterized in that: The specific surface area of ​​heat-insulating and water-insulating materials is greater than 0.1m 2 / g, porosity greater than 30%.

15. The double-glass assembly according to claim 13, characterized in that: The average particle size of the heat-proof and water-insulating material is less than 10 μm.

16. The double-glass assembly according to any one of claims 13 to 15, characterized in that: The heat-insulating and water-isolating materials include zeolite and / or inorganic molecular sieve.

17. The double-glass assembly according to any one of claims 13 to 15, characterized in that: The thickness of the heat-resistant and water-insulating material layer is 0.5-3.2 mm; And / or the width of the heat-resistant and water-insulating material layer is 2-10 mm.

18. The method for manufacturing a double-glass component according to any one of claims 12 to 17, characterized in that: The production method comprises: The composite sealing material is first placed between the front glass and the back glass, and then laminated. After the lamination is completed, the sealing slurry film in the composite sealing material is laser sealed with the front glass and the back glass to seal the front glass, the back glass and the composite sealing material into a whole to obtain the double glass assembly.

19. The manufacturing method according to claim 18, characterized in that: The production method further comprises: First, a heat-resistant and water-insulating material layer is placed between the front glass and the back glass and close to the side wall of the battery pack. Then, the composite sealing material is placed between the front glass and the back glass and close to the heat-resistant and water-insulating material layer, and then laminated. After lamination, the sealing slurry film in the composite sealing material is laser-sealed with the front glass and the back glass to seal the front glass, the back glass and the composite sealing material into a whole to obtain the double-glass component.

Citation Information

Cited By

  • Composite sealing material and preparation method therefor, and double-glass assembly and manufacturing method therefor

    WO2026118962A1